FOREIGN ECONOMIC ACTIVITY OF ENTERPRISES: METHODOLOGY OF EFFICIENCY, INNOVATION AND INVESTMENT CONTEXTS CONTEXTS IN A SECURE DIMENSION - VIVCHAR, Oksana; REDKVA, Oksana; TRUFANOVA, Yuliia; GEVKO, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Current issues of improving the foreign economic activity of domestic producers are considered. The main possibilities of entering the international market are substantiated. The main components of state policy in the foreign economic sphere have been identified. A practical mechanism for determining the economic efficiency of foreign economic activity of enterprises is presented. On the basis of this, the main ways of increasing the efficiency of foreign trade activities of domestic enterprises are proposed.